MODAL VALUES OF VERBAL FORMS IN THE EUROPEAN CHARTER FOR REGIONAL OR MINORITY LANGUAGES. A LINGUISTIC COMPARATIVE ANALYSIS OF THE ENGLISH, ITALIAN AND SPANISH VERSIONS - COPPOLELLA, Mariangela (Comparative Legilinguistics, 2014)
The present paper analyses the verbal expression of deontic, epistemic and performative values in the English, Italian and Spanish versions of the European Charter for Regional or Minority Languages, a treaty of the Council of Europe which aims to protect and promote the historical regional or minority languages of Europe. The objective of this paper is to show that Legal English, Legal Italian and Legal Spanish express in a different way the deontic, epistemic or performative values of verbal constructions, in particular recurring, or not, to modal verbs or to specific tenses. The results of the paper reveal that Legal English frequently uses modal verbs to express deontic or epistemic modalities of verbal forms, whereas it privileges indicative tenses to express performative modality; Legal Italian prefers indicative tenses to convey deontic and performative modalities, and subjunctive tenses to convey epistemic modality; Legal Spanish privileges indicative tenses to express deontic and performative modalities, and subjunctive tenses to express epistemic modality.